Los Dispositivos Electrónicos como Medida Sustitutiva a la Prisión Preventiva, lejos de Encaminarse a la Resocialización, van de Cabeza a la Reincidencia - Espinoza Poma, Jennifer Alexandra (2018)
The present research work is the analysis of the legal reality of the application of the electronic surveillance device as a substitute measure to preventive detention, far from heading for re-socialization go from head to recidivism, it is a precautionary measure replacing pre-trial detention that is established in the Organic Penal Code (COIP), in its article 522 number 4 of the COIP, in relation to the use of electronic surveillance device, as a measure of rehabilitation to the offender which will allow him to continue with his daily life, to be able to reinsert it into society and prevent it from re-offending. The analysis begins with a brief review of the important aspects of this study, such as: antecedents, electronic devices and preventive detention, custodial sentences, electronic devices, advantages and disadvantages, principle of re-socialization, causes that affect recidivism. These fundamental facts will serve as basic guidance to know and analyze from the legal field; the benefits of having implemented the electronic surveillance device as a substitute measure for pretrial detention, the effects of the application of electronic devices such as electronic bracelets that are currently being placed on people sentenced to a penalty of no more than five years , people of third age, and people with catastrophic illnesses as well as those who have served 60% of the sentence and people who are victims of family violence.